2014
DOI: 10.4049/jimmunol.1401467
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Gain-of-Function Mutations of STAT1 Responsible for Chronic Mucocutaneous Candidiasis Disease: Impaired Production of IL-17A and IL-22, and the Presence of Anti–IL-17F Autoantibody

Abstract: Heterozygous gain-of-function (GOF) mutations of STAT1 are responsible for chronic mucocutaneous candidiasis disease (CMCD), one of the primary immunodeficiency diseases characterized by susceptibility to mucocutaneous Candida infection. To date, 30 aa changes have been reported: 21 in the coiled-coil domain and 9 in the DNA-binding domain. In this study, we report two novel STAT1 GOF mutations of p.K278E in coiled-coil domain and p.G384D in DNA-binding domain in Japanese CMCD patients. Ectopic expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 27 publications
5
41
0
1
Order By: Relevance
“…40 In patients with CMCD, STAT1 GOF mutations are associated with a characteristic delay of protein dephosphorylation, resulting in persistent activation of the signaling pathway. 5,18,24,25 In our study the time course analysis of STAT1 phosphorylation in response to IFN-a has shown a similar pattern in NK cells of patients with STAT1 GOF mutations. However, we have also observed that both resting and IL-2-activated NK cells of these patients display increased STAT1 protein levels and higher expression of STAT1 mRNA, suggesting that augmented STAT1 protein levels might concur with the increased response of NK cells to cytokines signaling throughout STAT1.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…40 In patients with CMCD, STAT1 GOF mutations are associated with a characteristic delay of protein dephosphorylation, resulting in persistent activation of the signaling pathway. 5,18,24,25 In our study the time course analysis of STAT1 phosphorylation in response to IFN-a has shown a similar pattern in NK cells of patients with STAT1 GOF mutations. However, we have also observed that both resting and IL-2-activated NK cells of these patients display increased STAT1 protein levels and higher expression of STAT1 mRNA, suggesting that augmented STAT1 protein levels might concur with the increased response of NK cells to cytokines signaling throughout STAT1.…”
Section: Discussionsupporting
confidence: 75%
“…This observation is in accordance with previous studies showing a characteristic delay of STAT1 dephosphorylation. 5,18,24,25 Moreover, we investigated STAT1 protein levels in primary resting NK and T cells from patients with STAT1 GOF mutations. Surprisingly, flow cytometric analysis of STAT1 protein showed a 3-fold increase in STAT1 protein levels in resting NK and T cells from patients compared with protein levels detected in cells of healthy control subjects (Fig 1, F, and see Fig E1, E).…”
Section: Stat1 Phosphorylation In Nk Cells Of Patients With Stat1 Gofmentioning
confidence: 99%
“…CMC typically begins in early childhood, although it may first present up to the third decade of life, and signs and symptoms varied within and between families. 20 In these patients, CMC is most likely the consequence of impaired IL-17A and IL-17F immunity, [19][20][21]23,39,42,44 as it is also seen in patients with inborn errors of IL-17A/F immunity. [16][17][18] Circulating IL-17A-producing T cells counts are low in most but not all patients tested (82%).…”
Section: Discussionmentioning
confidence: 99%
“…Some genetic etiologies of CMC have been well-described, mutations in some genes like: AIRE, STAT1, STAT3 (2,4,11,12,13,14,15,16,17) Other genetic syndromes are associated with far smaller numbers of cases, such as those due to mutations of IL-17RA, ACT1, IL-17F, PTPN22, CLEC7A, TLR3, CARD 9 (5,6,10,11,12,19,20,21,22,23). There are distinct forms of CMC for which the genetic defects have not yet identified (24).…”
Section: Physiopathology Findings In Patients With Cmc and Potential mentioning
confidence: 99%